2010
DOI: 10.1194/jlr.m006973
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor-B1 and luteal function in mice

Abstract: This article is available online at http://www.jlr.org augmentation of the supply is by importation of lipoprotein-bound cholesterol ( 1 ). Low-density lipoproteins enter cells by receptor-mediated endocytosis of the LDL complex and the LDL receptor (LDLR) ( 2 ). High-density lipoproteins interact with a membrane protein known as scavenger receptor-B1 (SCARB1) to effect the selective uptake of cholesterol esters from the HDL molecule into cells and the bidirectional transfer of free cholesterol ( 3 ). The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 34 publications
3
26
0
Order By: Relevance
“…SR-B1 expression is essential for maintaining normal ovarian cholesterol homeostasis and luteal steroid synthesis (Jimenez et al, 2010;Miranda-Jimenez and Murphy, 2007). Data in this study showed that SR-B1 expression in the ovary grew up during proestrus and estrus.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…SR-B1 expression is essential for maintaining normal ovarian cholesterol homeostasis and luteal steroid synthesis (Jimenez et al, 2010;Miranda-Jimenez and Murphy, 2007). Data in this study showed that SR-B1 expression in the ovary grew up during proestrus and estrus.…”
Section: Discussionmentioning
confidence: 77%
“…Besides, SR-B1 mRNA expression reached its highest level at metoestrus in the new CL then gradually declined; while in the old CL, it was consistently high throughout the estrous cycle (Taketa et al, 2012). Moreover, SR-B1 expression appeared to be similar as follicles developed from proestrus to estrus, and expression increased drastically following luteinization in mice (Jimenez et al, 2010). Our results demonstrated that the expression levels of SR-B1 mRNA and protein were consistent and were highest during metoestrus and lowest during diestrus in the ovary.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations